User Experience Analysis on Student Services Website using User Experience Questionnaire (UEQ) KPI and Importance Performance Analysis (IPA) (Case Study: UPN "Veteran" Yogyakarta) - Vivo Putri Wenerda; Yuli Fauziah (Telematika, 2023)
Purpose: This study aims to obtain an end-user assessment of User Experience on the Student Services website so that it can be used as a priority material for improvement for the Bureau of Academic, Student Affairs, Planning, and Cooperation (AKPK) of the National Development University (UPN) "Veteran" Yogyakarta, when developing a website further.Design/methodology/approach: The User Experience Assessment on the Student Services website refers to 6 aspects of the assessment of the User Experience Questionnaire (UEQ) KPI method. The existing results will be mapped into an IPA (Importance Performance Analysis) diagram.Findings/result: The results of user experience testing on the Student Services website using the UEQ method, get the Good category for the Efficiency (1.56) and Dependability (1.57) aspects, the Above average category for the Attractiveness aspect (1.28), Perspicuity (1.57), and Stimulation (1.15) and the Bad category on Novelty (-0.27). Mapping the results of the UEQ KPI to the IPA quadrant, getting the results of the Attractiveness, Perspicuity, Efficiency, and Dependability aspects are in Quadrant 1, the Stimulation aspect is in Quadrant 2, the Novelty aspect is in Quadrant 3, and no aspect is in Quadrant 4. Based on the results of the study, it can be concluded that the user experience value of the end user is good. Recommendations for improvement priorities for the Student Services website can further prioritize Novelty aspels that are in Quadrant 3 and in Bad condition.Originality/value/state of the art: The focus of this research is the same as previous research, namely analyzing User Experience with reference to the assessment aspects of the KPI User Experience Questionnaire (UEQ) and IPA (Importance Performance Analysis) methods. The difference that can be seen in this study is from the implementation of the method into different case studies with the objectives and urgency and problems described in accordance with the existing research object.